The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra07042g
|View full text |Cite
|
Sign up to set email alerts
|

Tinospora cordifolia derived biomass functionalized ZnO particles for effective removal of lead(ii), iron(iii), phosphate and arsenic(iii) from water

Abstract: Owing to the vast diversity in functional groups and cost effectiveness, biomass can be used for various applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Several scientific reports are available to substantiate that T. cordifolia will absorb the heavy metals from the soil and store them in its parts. Sahu [29] reported that T. cordifolia is a biosorbent used for removing cadmium ions from industrial effluents [30]. Another study conducted by Vyas [30] reported that T. cordifolia effectively removes lead, iron, phosphate, and arsenic from water [31].…”
Section: Scientific Proof Of Heavy Metal Absorption By T Cordifoliamentioning
confidence: 99%
See 1 more Smart Citation
“…Several scientific reports are available to substantiate that T. cordifolia will absorb the heavy metals from the soil and store them in its parts. Sahu [29] reported that T. cordifolia is a biosorbent used for removing cadmium ions from industrial effluents [30]. Another study conducted by Vyas [30] reported that T. cordifolia effectively removes lead, iron, phosphate, and arsenic from water [31].…”
Section: Scientific Proof Of Heavy Metal Absorption By T Cordifoliamentioning
confidence: 99%
“…Sahu [29] reported that T. cordifolia is a biosorbent used for removing cadmium ions from industrial effluents [30]. Another study conducted by Vyas [30] reported that T. cordifolia effectively removes lead, iron, phosphate, and arsenic from water [31]. In the case of T. Cordifolia, the heavy metals will be accumulated in the warty tubercles seen on the stems.…”
Section: Scientific Proof Of Heavy Metal Absorption By T Cordifoliamentioning
confidence: 99%